Hindbrain mineralocorticoid mechanisms on sodium appetite - Formenti, Silmara [UNIFESP] (2013)
Formenti S, Bassi M, Nakamura NB, Schoorlemmer GHM, Menani JV, Colombari E. Hindbrain mineralocorticoid mechanisms on sodium appetite. Am J Physiol Regul Integr Comp Physiol 304: R252-R259, 2013. First published November 28, 2012; doi:10.1152/ajpregu.00385.2011.-Aldosterone acting on the brain stimulates sodium appetite and sympathetic activity by mechanisms that are still not completely clear. in the present study, we investigated the effects of chronic infusion of aldosterone and acute injection of the mineralocorticoid receptor (MR) antagonist RU 28318 into the fourth ventricle (4th V) on sodium appetite. Male Wistar rats (280-350 g) with a stainless-steel cannula in either the 4th V or lateral ventricle (LV) were used. Daily intake of 0.3 M NaCl increased to 46 +/- 15 and 130 +/- 6 ml/24 h after 6 days of infusion of 10 and 100 ng/h of aldosterone into the 4th V (intake with vehicle infusion: 2 +/- 1 ml/24 h). Water intake fell slightly and not consistently, and food intake was not affected by aldosterone. Sodium appetite induced by diuretic (furosemide) combined with 24 h of a low-sodium diet fell from 12 +/- 1.7 ml/2 h to 5.6 +/- 0.8 ml/2 h after injection of the MR antagonist RU 28318 (100 ng/2 +/-mu l) into the 4th V. RU 28318 also reduced the intake of 0.3 M NaCl induced by 9 days of a low-sodium diet from 9.5 +/- 2.6 ml/2 h to 1.2 +/- 0.6 ml/2 h. Infusion of 100 or 500 ng/h of aldosterone into the LV did not affect daily intake of 0.3 M NaCl. the results are functional evidence that aldosterone acting on MR in the hindbrain activates a powerful mechanism involved in the control of sodium appetite.